Movement velocity as a determinant of actual intensity in resistance exercise - Yáñez-García, J. M.; Mora-Custodio, R.; Ribas-Serna, J.; González-Badillo, J. J.; Rodríguez-Rosell, D. (International Journal of Sports Medicine, 2022)
This study aimed to analyze the acute mechanical, metabolic and EMG response to five resistance exercise protocols (REP) in the full squat (SQ) exercise performed with two velocity conditions: maximal intended velocity (MaxV) vs. half-maximal velocity (HalfV). Eleven resistance-trained men performed 10 REP (5 with each velocity conditions) in random order (72-96 h apart). The REP consisted of three sets of 8-3 repetitions against 45-65% 1RM. The percent change in countermovement jump (CMJ) height, velocity attained with the load that elicited a ~1.00 m·s-1 (V1-load), surface EMG variables and blood lactate concentration were assessed pre- vs. post-exercise protocols. MaxV resulted in greater percent changes (delta: 12-25%) and intra-condition effect sizes (ES: 0.76-4.84) in loss of V1-load and CMJ height compared to HalfV (delta: 10-16%; ES: 0.65-3.90) following all REP. In addition, MaxV showed higher post-exercise lactate concentration than HalfV (ES: 0.46-0.83; p<0.05). For EMG variables, only the Dimitrov index resulted in relevant changes after each REP, with MaxV showing greater magnitude of changes (23-38%) than HalfV (12-25%) across all REP. These results suggest that voluntary movement velocity is a key aspect to consider since it clearly determines the overall training intensity during resistance exercise.